Sharpening the Role of Public Sector Budgeting as a Planning and Control Tool at the Ministry of Religious Affairs of West Nusa Tenggara Province - Desi Intan Berlianawati (Cita konsultindo, 2024)
This research aims to explore how the role of budgeting as a planning and control tool in the Ministry of Religious Affairs of West Nusa Tenggara Province. This research uses a qualitative study, where this research is conducted in order to conduct a review of the public sector budgeting process as a planning and control tool at the Ministry of Religious Affairs of NTB Province. The method used is content analysis. The results of this study concluded that the implementation of a performance-based budget system in the Office of the Ministry of Religious Affairs of West Nusa Tenggara has been implemented well in accordance with government policy, however, the results obtained still need to be improved continuously in order to respond to the increasingly high demands of public services. Keywords : Planning Tools, Control, Budget, Performance Based.